Assessing the Current Market of Sunscreen: A Cross-Sectional Study of Sunscreen Availability in Three Metropolitan Counties in the United States - Kyle T. Amber; Romi Bloom; Patrick Staropoli; Sonam Dhiman; Shasa Hu (Journal of Skin Cancer)
Sunscreen use is recommended for the prevention of sunburn and skin cancer. Little is known regarding sunscreen availability in high versus low income communities. We analyzed sunscreen availability in three large metropolitan counties to determine the relationship between availability and community demographics. We included sun care products in all pharmacies and supermarkets open as of July 2013 in representative high and low income zip codes in Cook County, Illinois, Miami-Dade County, Florida, and San Diego County, California. We recorded the percentage of tanning oil, sunscreens with a sun protection factor (SPF) < 15, SPF > 15, physical sunscreens, spray sunscreens, mean price per ounce (PPO), and mean SPF. Of the total products assessed, 11.0% were tanning oils, with physical sunscreens accounting for only 3.4% of the available sunscreens and 46.2% of sunscreens being spray-on. A comparison between higher and lower income zip codes demonstrated a significantly increased percentage of sunscreens with SPF < 15 in high income zip codes. Lower income zip codes had higher percentages of sunscreens with SPF > 15 and higher PPO, even when taking into account SPF. Further studies of sunscreen usage patterns in different populations must take into account sunscreen availability and price, as these significantly differ based on the community demographic.